Statistical sampling in the practical field of research Analytical study of a sample of Master`s theses in the Faculty of Education at Tishreen University - دلالة هيفاء (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The aim of the current research is to identify the foundations that were adopted - by master’s students in the Faculty of Education at Tishreen University - for statistical sampling, that is, choosing and determining the sample size in their studies. Thus, discovering the errors that they may make. In our research, we replied on the descriptive, analytical and evaluative method. Accordingly, we designed a form to collect research data and verify its psychometric properties. The study sample consisted of (153) Master`s theses that we were able to obtain. The results showed that the most used samples by researches are the simple random sample, with a (30.07%). In addition to the presence of a number of Master`s theses in which the researchers did not specify the type of sample used and their percentage (18.98%). It also became clear to us that the proportional estimation method for determining the sample size.